Halloween Costume Choices: Reflections of Gender Development in Early Childhood. Issue 3 (4th May 2017) - Dinella, Lisa M.
ABSTRACT: The author examined whether preschoolers' Halloween costume choices reflect their gender development. The sample consisted of 110 (53 boys, 57 girls) infant through preschool-aged participants, and 1 parent of each child. Both observational methodologies and parent-report surveys were used to assess the gender-typed nature of children's Halloween costumes, information about the Halloween costume choice process, and about the children's gender development. Boys' costumes were more masculine and girls' costumes were more feminine. Younger children's costumes were consistently less gender typed than the older children's costumes were. Children whose parents chose their Halloween costumes for them had Halloween costumes that were less gender typed than did children who were involved in the Halloween costume decision-making process. Moreover, children's gender-typed play and desire to wear gender-stereotyped clothes were related to the gender stereotyped nature of their Halloween costume. Unexpectedly, gender typicality, a dimension of gender identity, was not related to children's Halloween costume choices. Overall, the findings support that children's Halloween costume choice is an indicator of children's gender development processes.